2021
DOI: 10.1039/d1py00146a
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive glyco-nanostructures integrated from supramolecular metallocarbohydrates for the reversible capture and release of lectins

Abstract: The development of smart and controllable multivalent systems, which enable us to control the interactions at the biological system-artificial material interface, is of great scientific and technological interest. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Simultaneously, due to the inherent cavity of the macrocycles which can well protect the inclusion, Yao and co-workers created a pillar [5]arene-based host-guest system 19,65 to improve the stability and fluorescence intensity of the dyes, and Ma et al used the same approach to brighten and enlarge the emission of Au nanoclusters and for cancer cell imaging. 46 Most importantly, owing to the considerable biocompatibility and inherent inclusion of macrocycles, strategies based on host-guest assembly have been widely used in recent years for constructing drug delivery systems, 66,67 synthesizing antimicrobial materials, 44,[68][69][70] and designing biomedical reagents. [71][72][73][74] This paper will focus on the development and biological applications of host-guest strategies in fluorophore-based bioimaging and therapeutic reagents and their potential challenges and prospects.…”
Section: Properties and Applications Of Fluorophore-macrocycle Complexesmentioning
confidence: 99%
“…Simultaneously, due to the inherent cavity of the macrocycles which can well protect the inclusion, Yao and co-workers created a pillar [5]arene-based host-guest system 19,65 to improve the stability and fluorescence intensity of the dyes, and Ma et al used the same approach to brighten and enlarge the emission of Au nanoclusters and for cancer cell imaging. 46 Most importantly, owing to the considerable biocompatibility and inherent inclusion of macrocycles, strategies based on host-guest assembly have been widely used in recent years for constructing drug delivery systems, 66,67 synthesizing antimicrobial materials, 44,[68][69][70] and designing biomedical reagents. [71][72][73][74] This paper will focus on the development and biological applications of host-guest strategies in fluorophore-based bioimaging and therapeutic reagents and their potential challenges and prospects.…”
Section: Properties and Applications Of Fluorophore-macrocycle Complexesmentioning
confidence: 99%
“…For example, Percec et al synthesized a variety of amphiphilic Janus glycodendrimers via an accelerated modular synthetic strategy, which were capable of self-assembling into various glyco-nanostructures including glyco-dendrimersomes, disks, and cubosomes, displaying qualitative differences from linear amphiphilic polymers, for the biomimicry of cell membranes. Martin and co-workers prepared a family of C 60 -centered precise glycodendrimers with different generations and saccharide units, which further aggregated into larger glyco-nanostructures for the applicability of antiviruses. , Very currently, we studied the self-assembly of a new class of amphiphilic dendritic supramolecular metallocarbohydrates with tunable and symmetric architectures and different saccharide units. It was found that the morphologies (vesicles, micelles, glycoworms, tubes, and anisotropic open vesicles) of generated glyco-nanostructures in aqueous solution could be effectively modulated by the balance of carbohydrates and metallocycles. However, although great achievement has been made in the fabrication of glyco-nanomaterials from self-assembly of amphiphilic glycodendrimers, the synthesis of dendritic glycopeptides and their self-assembly properties have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%